Pulmonary Infection - Pokorski, Mieczyslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The respiratory tract is a frequent target of infections caused by a wide range of organisms. The book provides reader-friendly information on aspects of pulmonary infections, including comprehensive accounts of bacterial and viral diseases, therapeutic approaches, molecular and classical culture-related techniques of diagnosis, and explaining the basic cell biological mechanism. The role of oxidative stress, both helpful in fighting invading pathogens and detrimental in yielding to infection is detailed as it is often undervalued and needs focus. The chapters encompass latest developments and applications in bacteriology and virology, preventive and therapeutic tips, and raise attention to implementation of proper antibiotic policies by medical institutions to decrease resistance to antimicrobials. The perennial problem of low influenza vaccination coverage rate is rationalized. The volume will be of interest to both clinicians and biomedical researchers engaged in this exciting field.
Evaluation of the Activity of Influenza and Influenza-like Viruses in the Epidemic Season 2013/2014 -- Necrotizing Pneumonia and its Complications in Children -- Progress in the Diagnosis and Control of Ebola Disease -- Pathophysiology of Clinical Symptoms in Acute Viral Respiratory Tract Infections -- Stagnating Low Influenza Vaccine Coverage Rates in the Polish Elderly Population in 2008-2013 -- Incidence of Circulating Antibodies against Hemagglutinin of Influenza Viruses in the Epidemic Season 2013/2014 in Poland -- Neutrophils - the role of oxidative and nitrosative stress in health and disease -- The Incidence of Respiratory Tract Infections in Vertically HIV-Infected Children in Lower Silesia in Poland and the Approach to Infection Prevention -- Implementation of Hospital Antibiotic Policy Decreases Antimicrobial Use in the Pediatric Ward -- Detection of Chlamydophila Pneumoniae and Typical Bacteria in Patients with Chronic Cough -- Compliance with Vaccination Against Influenza Among the Elderly.
Keywords: Virology; Infectious diseases; Life sciences; Virology; Infectious Diseases; Life Sciences, general